Teachers' Knowledge of Juvenile Delinquency and Its Prevention: A Comparative Study of Private and Government Schools in Gurugram, Haryana - Tamanna,; Anjali,; Geetika,; Bhoomika,; Nicky Tyagi, (The Bioscan, 2025)
Introduction: Juvenile delinquency remains a significant concern in educational settings, as it affects the well-being of students and the overall school environment. Teachers, being at the forefront, play a crucial role in recognizing and addressing delinquent behaviour. This study aimed to compare the knowledge of teachers from private and government schools in Gurugram, Haryana, regarding juvenile delinquency and its prevention. Methodology – This descriptive study involved 100 teachers (50 from private schools and 50 from government schools) in Gurugram, Haryana. A purposive sampling technique was used for selecting participants. Data were collected through a structured questionnaire that included demographic factors such as age, gender, marital status, education, teaching experience, socio-economic status, and prior professional development on juvenile delinquency and self-report knowledge questionnaire. Findings – The study found that a majority of teachers from both private (38%) and government schools (52%) had moderate to adequate knowledge regarding juvenile delinquency. Government school teachers showed better knowledge, with a higher percentage demonstrating adequate understanding (52%) compared to private school teachers (30%). Furthermore, 72% of private school teachers and 74% of government school teachers had not received any professional training on juvenile delinquency. The study also indicated that teaching experience influenced the knowledge level, particularly in private school teachers. Conclusion: The study highlights the need for more targeted professional development programs on juvenile delinquency for both private and government school teachers. Strengthening teachers' knowledge and preparedness can help improve the management and prevention of juvenile delinquency in schools.